An Analysis of Effective Factors on Spatial Distribution of Poverty in Rural Regions of Hamedan Province - Peirovedin, Mohammad-Reza; Mahdavi, Masood; Ziyari, Yousef-ali (International Journal of Geography and Geology, 2016)
The aim of this paper is to examine the spatial distribution of poverty in order to show the effects of poverty rate of a region on the poverty of other rural regions of Hamadan province by making use of spatial econometric approach. The statistical population of the study included 383 rural households participating in the survey of household expenditure and income in 2012 is nine cities of Hamedan province. To analyze the data and to provide the poverty map, Spatial Econometrics and Matlab software and GIS were used as research tools. Initially, the poverty line and the estimated volume of poverty and deprivation were calculated and then, by measuring its volume, the distribution of poverty of the regions and its influence in the cities of the province were provided. Moran’s I-statistic was obtained for poverty equals 0.211 which is significant at the 1% level and shows spatial autocorrelation. Poverty is not distributed equally in rural regions of Hamadan province and the geographical location of households living in the rural areas is effective on poverty. The results of the research showed that in calculating the model by Ordinary Least Squares (OLS) methods and spatial errors due to the spatial dependence in error terms, spatial error methods is better results than the OLS method. Variables such as average household size (+), gender of household head (-) and the proportion of households with housing (-) are statistically significant in identifying the poor people at less than 1% level and the type of jobs (+) at the 5% level respectively.